(untitled) (Práxis Educativa, 2025)
This article examines how contemporary social organization, under the aegis of neoliberalism, has intensified and precarized academic labor in Brazil’s public stricto sensu graduate programs, contributing to professors’ psychological distress. Drawing on a theoretical-analytical approach informed by Zygmunt Bauman, Theodor W. Adorno, Max Horkheimer, and Christophe Dejours, the study discusses how productivist and market-oriented logics shape the emotional exhaustion of faculty who face constant pressure for productivity, excessive workloads, and a lack of institutional recognition. The research shows that current academic evaluation systems, by prioritizing quantitative performance metrics, reinforce excessive competitiveness and alienation in academic work, deepening mental suffering within universities. In light of this scenario, the article argues for the need to rethink graduate evaluation policies in order to mitigate the negative impacts of this model and foster a more sustainable and humanized academic environment. Keywords: Precarization of academic work. Graduate education. Psychological distress.